DOĞRUSAL PROGRAMLAMA METODUYLA DİYARBAKIR İLİ GIDA SEKTÖRÜNDE BİR ÜRETİM PLANLAMA UYGULAMASI. - KARA, Hasan; SAVAŞ, Halil (Electronic Turkish Studies)
Production is one of main functions of organizations. Companies, intending to increase their profit by using their sources efficently, must produce their goods according to a certain plan and program. Production planning is the product goal within the planning period. It is the decision period that states the future projection for production by considering the current resources. Demand of product, quality of product, price of product, raw material, market, customers satisfaction and capacity of company, are all evaluated during production planning period. One of the most efficient methods used in production planning is linear programming. Linear programming, has become a standard method of decision making for input, marketing and transport planning in the production planning. By considering current resources of an organization, the production planning enables us determining the optimum level to supply necessary products. Simplex method, as a solution method of linear programming models, is used to find optimum amount of production of the company in a food organization in city of Diyarbakir in Turkey. The model, constructed by simplex method, is formed by goal function and constrait equations. The main goal of constructed model by suitable amount of production is maximum profit. From the data and results, it is observed that adjusting necessary labor force for predicted amount of products increases the profit of this food company. Although many studies based upon linear programming are dedicated for solving problems of production and control of many sectors, such as food, textile, oil, insurance and agriculture, a limited number of studies has been conducted only for food industry. This is the reason why this study by using tools of linear programing concentrates on the production planning in food sector. The reasons for selection of the city of Diyarbakır and the food company are listed as follows; ï,· Historical, cultural and economic potantial of Diyarbakır, ï,· Lack of analysis about production of 'kadayıf' and 'baklava,' that are traditional desserts, ï,· To show increasing export potential of many kinds of baklavaand kadayıf. Hacı Levent Kadayıfçısı Gıda İnşaat Ltd. Şti. is a company located in the city of Diyarbakır was choosen for production planning in this study. A model of production planning developed for this company producing baklava and kadayıf over many years can be a good example to other companies that operates in same sector. Basic steps of this study are itemized as the following. At the initial phase, decision variables are identified in the model. The definition of 14 kinds of baklava and kadayıf for the production planning is given below; As is well known, during the production period, data of previous and next term make easier to analyze the demand of customers. Periodic statistical data that are related to previous production period is taken from accounting manager of the company. A production model was created using these data. A very important and necessary condition for customers is the freshness of the food in food industry. Otherwise, the food company will loose its market and customers. For these reasons, the organization always has to keep the products fresh. From the data, it is also observed that the company should have produced a very wide range of desserts with expense of less profit or even of loss. In this respect, the constraits of production of company in view of production, demand and tecnology can be listed as follows; ï,· Production time spans from 1 March 2013 to 1 June 2013, 90 days in total, ï,· There is no stock of the company at the beginning of the production period, ï,· Number of machines and labor force during the production period are not changed. ï,· Labors work 49 hours in a week.10 of 25 labors are allocated for baklava production and the rest of them work in kadayıf production, ï,· The demand of manufacture of kadayıf and baklava is very dynamic and changes with customer orders. It should be pointed out that stock of raw materials and semi-finished used in the production does not affect the model, ï,· The present capacity of the company is at most 56,250 kg of desserts in a production period, ï,· In the previous period, the company had sold more than 810 kg of x5. Along with other products in line with the market demand, the company has produced at least 248 kg of x12 and at least 450 kg of x14. ï,· According to market demand of previous production period, the amount of x1 is 5 times more than the amount of x2. Despite the lack of demand of x10 in the business market, 450 kg of x10 is determined to product. Production quantities was obtained in the solution of the model by linear programming. In this case, the maximum profit of the company is â,°210,080. The most remarkable point was problem of production of x under the current constraints. The company couldn't have produced enough amount of market demand of x, therefore, it was faced with the risk of losing customers. This issue has been solved by adding 50220 minutes to the labor force of kadayıf section. From the results of the model in production period, when 21600 kg of x, 4320 kg of x, 1080 kg of x, 1440 kg of x, 810 kg of x, 630 kg of x, 2700 kg of x, 900 kg of x, 900 kg of x, 450 kg of x, 540 kg of x, 248 kg of x, 1125 kg of x and 450 kg of x are produced, the profit of the company is maximum. The amount of profit of the model increases from â,°210,080 to â,° 227,657. Profit growth of the company (â,°17577) is realized as 8%. If predictions of the model is taken account, it can be concluded that the business should consider to produce the products range that customers like and satisfy. From the results, X12 and X14 must be produced at the lowest rate. Although some products were demanded in the past, their profits seem to be low enough in the production period that we analyzed. For this reason, to increase profit, the model shows that no more amount of such kind of products should be produced other than zero at all. This requirement is considered to be in the future. This approach improving competitiveness in the long term is expected to provide high profits. So, instead of maximizing profit by increasing the production amount of some specific products, the aim would be to produce appropriate amounts of all the products. It is clearly expressed as a result of this study, the company can develop itself in two remarkable points. First, in the present case, the entity is engaged in labor force for optimum production. If labor force is increased in kadayıf section as of 50220 minutes, the maximum profit will be made. The rate of labor force 50220 minutes divided by worker force 37800 that is equal to 1.32 means that the company normally has to employ more than a worker. The workers has affected negatively intensive physical labor required in the production process in the long term. To increase the production of the company in an increasingly competitive environment, the organization have to make necessary changes in production and employ experienced and satisfied workers. The second important point is that the amount of production must be increased by targeting full capacity. It is necessary to increase its market share to reach this production level. To increase market share, it is possible to reach more customers by increasing their sales points in all provinces across the country. Besides sales points, the ease of shopping from internet can increase the possibility of selling and profit of the company. The designed model will be able to make an important contribution to the companies that operate in the food industry across the country. The model can be common practice and benefits in the sector. By means of the model, the company will be able to predict future employment needs in the sector. The production planning prepared for the manufacture of kadayıf and baklava is believed to lead to new studies in the future.